Pengembangan E-Modul Berbasis Metode Inkuiri Pada Materi Pecahan Kelas IV SD - Ade Sari Oktavia; Siti Quratul Ain (IJoIS: Indonesian Journal of Islamic Studies, 2022)
This development research aims to develop E-Module teaching materials that are suitable for use in learning mathematics on equivalent fractions. This development research uses the ADDIE research method. This research is focused on three stages. Analysis Phase (1), which includes an analysis phase consisting of analysis of teacher and student needs, curriculum analysis and analysis of learning materials, Design Phase (2) the design phase of designing lesson plans, designing conventional modules in word, converting conventional modules into PDF, and changing the PDF module into an E-Module form, as well as the Development stage (3) which includes the validation and revision stages of the product. The subjects in this study were 2 material experts, 2 linguists, and 2 design experts. The instrument used is a validation sheet and the data analysis techniques used are quantitative and qualitative. The results obtained from the development of the E-Module based on the inquiry method on grade IV elementary school fraction materials that are suitable for use based on the assessment of material experts 91% with very feasible criteria, linguists 87.77% with very feasible criteria, design experts 96.3% with very decent criteria. The average percentage of validation results is 91.69% with very feasible criteria without revision.